Effect of Reduced Soil pH with Sulfur on Available Soil Phosphorus in High pH Sandy Soils of South Florida - Kelly T. Morgan; Kamal Mahmoud (EDIS, 2014)
This 3-page fact sheet addresses the effect of moderating soil pH by using sulfur amendments in high pH soils and discusses their relationship to both nutrition and fertilizer management. Written by Kelly T. Morgan and Kamal Mahmoud, and published by the UF Department of Soil and Water Science, December 2013.